2004
DOI: 10.1007/s00167-003-0426-z
|View full text |Cite
|
Sign up to set email alerts
|

Tunnel enlargement and changes in synovial fluid cytokine profile following anterior cruciate ligament reconstruction with patellar tendon and hamstring tendon autografts

Abstract: There is growing evidence that cytokines such as tumor necrosis factor (TNF) alpha, interleukin (IL) 1beta, IL-6, bone morphogenetic proteins (BMP), and nitric oxide (NO) play an important role in the pathogenesis of bone tunnel enlargement following anterior cruciate ligament (ACL) reconstruction. Furthermore, the release of these mediators has been considered a possible reason for the higher incidence of bone tunnel enlargement following hamstring tendon (HST) than following patellar tendon (PT) ACL reconstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
112
0
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(115 citation statements)
references
References 25 publications
1
112
0
2
Order By: Relevance
“…The biological theory states that release of TNF, interleukins, and nitric oxide present in the synovial fluid can cause osteolysis. The mechanical reasons for tunnel widening are graft tunnel micro motion in suspensory fixation, stress shielding proximal to the interference screw and nonantomical graft fixation [18,19,20] . As menisci along with cruciate ligaments also has important role in biomechanical stability, we have tried to evaluate incidence of tunnel widening and knee instability after ACL reconstruction and compare them in two groups: those with meniscal repair and those with without repair.…”
Section: Resultsmentioning
confidence: 99%
“…The biological theory states that release of TNF, interleukins, and nitric oxide present in the synovial fluid can cause osteolysis. The mechanical reasons for tunnel widening are graft tunnel micro motion in suspensory fixation, stress shielding proximal to the interference screw and nonantomical graft fixation [18,19,20] . As menisci along with cruciate ligaments also has important role in biomechanical stability, we have tried to evaluate incidence of tunnel widening and knee instability after ACL reconstruction and compare them in two groups: those with meniscal repair and those with without repair.…”
Section: Resultsmentioning
confidence: 99%
“…Possible factors responsible for bone resorption include mechanical theory which states that there is a micromotion of the graft relative to the tunnel wall which causes synovial fluid bathing of the graft, leading to an inflammatory response in the tunnel. Also stress shielding of the tunnel wall proximal to the interference screw can cause weakening of the bone [6,20,21] Biological factors include nonspecific inflammatory response cells, heat necrosis due to drilling, cytokine response like TNF, interleukin-6, nitric oxide from the synovial fluid and foreign body response to allograft [22,23] There are different patterns of osteolysis at tibial tunnel described by Peyrache where patellar tendon bone graft was fixed with screw. These are cone type, cavity type and line type [7] We evaluated similar changes in our patients and tried to evaluate its clinical and functional correlation.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of IL-1β in the normal human synovial fluid is 10±4.3 pg/ml [4,5,10,18,25]. Several magnetic resonance imaging studies have shown synovial fluid tracking between the graft-bone tunnel interface [25].…”
Section: Discussionmentioning
confidence: 99%
“…Several magnetic resonance imaging studies have shown synovial fluid tracking between the graft-bone tunnel interface [25]. The bone tunnel is subsequently exposed to increased levels of cytokines within the synovial fluid possibly inducing osteolysis [3,13,15].…”
Section: Discussionmentioning
confidence: 99%